3x+12-4=

Simple and best practice solution for 3x+12-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+12-4= equation:


Simplifying
3x + 12 + -4 = 0

Reorder the terms:
12 + -4 + 3x = 0

Combine like terms: 12 + -4 = 8
8 + 3x = 0

Solving
8 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 3x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 3x = 0 + -8
3x = 0 + -8

Combine like terms: 0 + -8 = -8
3x = -8

Divide each side by '3'.
x = -2.666666667

Simplifying
x = -2.666666667

See similar equations:

| -1/3x=-5/6 | | 3(5x-2)=19 | | M-4-3m=-2m-3-1 | | (13x-6)-6(2x+2)=-6 | | 400+300/20 | | 0.5x+6=x+5/3 | | 2/x-2=-4/x+4+18/(x-2)(x+4) | | 2u-54=-u+21 | | 8a=65-100n | | 400+(15x200)/200 | | (6h-7)/h | | (-7/12)-(-3/8)=0 | | 4x+32=4x+26 | | (17x-9)-8(2x+4)=-5 | | -7/12-(-3/8)=0 | | (10/11)x+(1/3)=(2/5)-(1/11)x+(2/5) | | y=2ZX+2ZY+2XY | | L=0.4L+6 | | -9h=u | | (2/3)x+(1/2)=(3/7)-(1/3)x+(3/7) | | (-2v/9)=-6 | | (-7/2y)=-21 | | [x+3]=7x-4 | | (-5/6v)=20 | | Y=4x-160 | | 5/3x+1/3x=131/3+8/3 | | ln(2x+14)-ln(x+2)=ln(x-5) | | 3(u-5)-9=-6(-2u+2)-u | | 1.89/12 | | 8(v+2)+3v+7=6v+7 | | -2(x-4)-20=-12 | | (5/4)^-3 |

Equations solver categories